A comparison of broad-spectrum and narrow-spectrum dry cow therapy used alone and in combination with a teat sealant - Bradley, Andrew J.; Breen, J.E.; Payne, B.; Green, Martin J. (American Dairy Science Association, 2011)
The dry period is a critical time in the lactation cycle, offering the optimum time for cure of existing intramammary infection (IMI), while also encompassing the periods of highest susceptibility to new intramammary infection. Until recent years, intramammary infection in the dry period has been controlled with the use of antibiotic dry cow therapy. The aim of this study was to investigate 3 different dry cow therapy regimens, in low-somatic cell count (SCC; bulk milk SCC < 250,000 cells/mL) herds in southwest England. A total of 489 cows was recruited to the study and randomly allocated to receive either the broad-spectrum antibiotic cefquinome, a combination treatment comprising the narrow-spectrum antibiotic cloxacillin and an internal teat sealant, or the narrow-spectrum antibiotic cloxacillin alone. All quarters were sampled for bacteriology at drying off and again in the week immediately postcalving; 2 quarters were also sampled 2 wk before the estimated calving date to allow an assessment of infection dynamics during the dry period. Quarters were subsequently monitored for clinical mastitis for the first 100 d of lactation. Conventional multilevel (random effects) models were constructed to assess the efficacy of products in preventing IMI. Survival analysis was used to examine factors that influenced the risk of clinical mastitis using conventional Cox proportional hazards models. No differences were identified between the treatment groups in terms of cure of IMI caused by the major pathogens. Quarters in both the combination and cefquinome-treated groups were more likely to be free of a major pathogen or enterobacterial pathogen postcalving. With respect to clinical mastitis, the cefquinome-treated group was less likely to develop clinical mastitis than was the cloxacillin treated group.